Biomarkers for early detection of ovarian cancer. (March 2013) - Nguyen, Long; Cardenas-Goicoechea, Segundo Joel; Gordon, Pierre; Curtin, Christina; Momeni, Mazdak; Chuang, Linus; Fishman, David
Ovarian cancer is the most lethal gynecological malignancy. However, effective screening strategies have not been established and continue to be elusive. A good screening test must adequately address validity, reliability, yield, cost, acceptance and follow-up services. An ideal screening test for ovarian cancer must have a high sensitivity in order to correctly diagnose all women with the disease and a high specificity to avoid false-positive results. The current screening modalities of bimanual examination, CA-125 and transvaginal ultrasonography together allow us to detect only 30–45% of women with early-stage disease. Recent developments in proteomic and genomic research have identified a number of potential biomarkers. Although panels of tumor markers and proteomic-based technologies may improve the positive predictive value, all markers require validation and interfacing with newly developed diagnostic imaging technologies. While a large amount of information on miRNAs has been promising, much remains to be elucidated. This review will examine the current status of biomarkers and technologies of interest in the effort of early detection of ovarian cancer.